Primulina liangwaniae (Gesneriaceae), a new species from Guangdong, China - Tong, Yi-Hua; Ni, Jing-Bo; Wang, Bing-Mou (Phytotaxa, 2023)
Primulina liangwaniae, a new species of Gesneriaceae endemic to Guangdong, China, is described and illustrated. The new species is close to P. versicolor in having similar shape and color of corollas, but differs in the significantly smaller leaf blades with dense spreading villus and pubescence and crenate margin, much shorter peduncles, smaller bracts with margin being crenate on upper part and entire on lower part, much shorter pedicels, and narrowly cordate stigma. The flowering times of these two species are also different. A provisional conservation status of DD (Data Deficient) is given for P. liangwaniae.